Outsourcing Turnover Analysis at PT Bank Negara Indonesia’s Digital Operational Division - Novitasari, Martha (KnE Social Sciences, 2022)
This study aimed to determine the factors causing an increase in turnover of outsourced employees at PT Bank Negara Indonesia’s Digital Operational Division and to find out what policies and strategic steps were taken to reduce this turnover rate. The researcher used qualitative approaches and data were collected through observations, document analysis and interviews with key informants including the Head of the Digital Operations Division, deputy leaders in charge of employees in the Digital Operations Division, leaders of support groups who were responsible for the availability of employees, supporting managers who directly oversaw outsourcing, employment provider companies, and outsourcing personnel who were still working as well as outsourced staff who had left. The research was conducted at PT Bank Negara Indonesia’s Digital Operational Division. It was found that there were intrinsic and extrinsic factors causing the increased turnover of outsourcing personnel. These intrinsic factors included the challenges of the job itself, work progression of promotion/rank, responsibility for the assigned job, recognition of work results, achievement, employee productivity, education, work experience and age. Meanwhile, extrinsic factors included administration and company policies as well as government regulations, supervision, salaries, interpersonal relationships, working conditions, supply and demand for the number of jobs with the availability of labor, attachment to the organization and corporate culture. Keywords: outsourcing, turnover